2020
DOI: 10.1002/mds.28312
|View full text |Cite
|
Sign up to set email alerts
|

Differences in the Presentation and Progression of Parkinson's Disease by Sex

Abstract: Background Previous studies reported various symptoms of Parkinson's disease (PD) associated with sex. Some were conflicting or confirmed in only one study. Objectives We examined sex associations to PD phenotypes cross‐sectionally and longitudinally in large‐scale data. Methods We tested 40 clinical phenotypes, using longitudinal, clinic‐based patient cohorts, consisting of 5946 patients, with a median follow‐up of 3.1 years. For continuous outcomes, we used linear regressions at baseline to test sex‐associat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
42
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 66 publications
(54 citation statements)
references
References 36 publications
10
42
2
Order By: Relevance
“…Importantly, studies have noted sex as a risk variable in the onset of cognitive impairment, both in PD and in other populations. However, there have been few previous comprehensive investigations of sex-based differences in individual cognitive domains over time [31], as in the present study. Some prior studies have been purely cross sectional in nature [5,9,10,12,[17][18][19], while longitudinal studies have not examined the sex-specific differences in various cognitive domains [20], or have not focussed primarily on elucidating the impact of sex on cognition [32].…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…Importantly, studies have noted sex as a risk variable in the onset of cognitive impairment, both in PD and in other populations. However, there have been few previous comprehensive investigations of sex-based differences in individual cognitive domains over time [31], as in the present study. Some prior studies have been purely cross sectional in nature [5,9,10,12,[17][18][19], while longitudinal studies have not examined the sex-specific differences in various cognitive domains [20], or have not focussed primarily on elucidating the impact of sex on cognition [32].…”
Section: Discussionmentioning
confidence: 74%
“…Furthermore, sex differences in microglial and astrocytic cells, such as their heightened sensitivity to inflammatory stimuli [42][43][44] and their anatomical distribution [45,46], have been postulated to mediate sex differences in cognition and memory [47,48]. It is worthwhile considering that such results may be reflective of the superior baseline performance of females in cognitive measures than males or may be exacerbated by disease process, though prior research has found that sexspecific progression to cognitive impairment cannot be fully explained by this baseline performance, nor disease duration [31].…”
Section: Discussionmentioning
confidence: 99%
“…27 Where on the phenotype level slight differences are observed between men and women in PD, DLB, and AD and overall men have a faster progression/ cognitive decline and shorter lifespan after diagnosis. 6,27 Sex-dependent autosomal effects on clinical progression of AD have been observed 28 and data on sex-dependent autosomal effects for other neurodegenerative diseases is lacking. Here, we assessed whether an autosomal genetic difference explains these differences by performing GWAS using several large case-control datasets and separating these by men and women.…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4][5] There are also differences in the clinical presentation of PD by sex, female patients are more likely to experience dyskinesia and a slower decline in performance of activities of daily living, whereas it has been shown that male patients have a higher risk of developing cognitive impairment. 6 Symptoms that present into the earliest phases of PD also differ by sex; rapid eye movement (REM) sleep behavior disorder (RBD) is much more common in men, and depression and anxiety appear to be more common in women. 7,8 PD is a genetically complex disease, with a substantial genetic component explained by rare and common variants.…”
mentioning
confidence: 99%
“…Possible explanations might include different degrees of exposure to environmental risk factors (such as pesticides and heavy metals), putative risk and protective factors (head trauma, caffeine and urate), the influence of sex-specific hormones, differential aging and life expectancy, or potential genetic factors, either linked or independent of these other factors (Nandipati and Litvan 2016;Gao et al 2016;Ascherio et al 2004;Taylor, Cook, and Counsell 2007). There are also differences in the clinical presentation of PD by sex, female patients are more likely to experience dyskinesia and a slower decline in performance of activities of daily living, while it has been shown that male patients have a higher risk of developing cognitive impairment (Iwaki et al 2020). Symptoms that present into the earliest phases of PD also differ by sex; REM sleep behaviour disorder (RBD) is much more common in males, and depression and anxiety appear to be more common in females (Postuma et al 2019;Shiba et al 2000).…”
Section: Introductionmentioning
confidence: 99%